2016
DOI: 10.1037/abn0000106
|View full text |Cite
|
Sign up to set email alerts
|

Altered subjective reward valuation among drug-deprived heavy marijuana users: Aversion to uncertainty.

Abstract: Marijuana is the most commonly used illicit drug in the United States and its use is rising. Nonetheless, scientific efforts to clarify the risk for addiction and other harm associated with marijuana use have been lacking. Maladaptive decision-making is a cardinal feature of addiction that is likely to emerge in heavy users. In particular, distorted subjective reward valuation related to homeostatic or allostatic processes has been implicated for many drugs of abuse. Selective changes in responses to uncertain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…For instance, Hogle et al (2010) have demonstrated that within smokers, nicotine deprivation selectively increases startle potentiation to an unpredictable threat and that both anticipating smoking a cigarette and actually smoking a cigarette significantly dampens this reactivity (Bradford et al, 2015). Meanwhile, heavy marijuana users have been shown to exhibit heightened aversive reactivity to an uncertain threat and an uncertain reward (Hefner et al, 2015; Gloria et al, 2015, in preparation), highlighting the possibility that substance users evidence a broad sensitivity to uncertainty and find unpredictable threats and rewards aversive. Taken together, reactivity to uncertainty, particularly an uncertain threat, has emerged as an important construct related to several forms of substance use and future studies should therefore continue to clarify its role in substance use initiation, maintenance and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hogle et al (2010) have demonstrated that within smokers, nicotine deprivation selectively increases startle potentiation to an unpredictable threat and that both anticipating smoking a cigarette and actually smoking a cigarette significantly dampens this reactivity (Bradford et al, 2015). Meanwhile, heavy marijuana users have been shown to exhibit heightened aversive reactivity to an uncertain threat and an uncertain reward (Hefner et al, 2015; Gloria et al, 2015, in preparation), highlighting the possibility that substance users evidence a broad sensitivity to uncertainty and find unpredictable threats and rewards aversive. Taken together, reactivity to uncertainty, particularly an uncertain threat, has emerged as an important construct related to several forms of substance use and future studies should therefore continue to clarify its role in substance use initiation, maintenance and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they identified potential individual-difference factors (e.g., binge drinking history, negative emotionality) that may moderate alcohol’s anxiolytic effects (Bradford et al, 2013; Hefner et al, 2013). Another feature of this research program is the degree to which the mechanisms of stimulus certainty or predictability have been contrasted across drugs of abuse (Hefner, Starr, & Curtin, 2016; Hogle, Kaye, & Curtin, 2010). The appeal of the shock threat paradigm is that there is more control over factors such as predictability than one would expect using more unwieldy social interaction manipulations.…”
Section: Negative Affect Reliefmentioning
confidence: 99%
“…For instance, subsequent studies should consider tasks that allow for a comparison of neural reactivity during the anticipation of unpredictable rewards relative to predictable rewards (Alkozei, Smith, & Killgore, 2016), which could involve manipulations of reward timing, probability, and/or amount. Second, to better simulate dynamics of the real world, studies could also consider tasks that manipulate rewards (or threats) in such a way that participants are able to learn various contingencies, make decisions regarding the potential for reward, and then use these estimates to inform their behavioral response (e.g., Hefner, Starr, & Curtin, 2015;Hsu, Bhatt, Adolphs, Tranel, & Camerer, 2005). This would ultimately allow for real-time assessments of aversion/preference for uncertainty and its impact on behavior.…”
Section: Discussionmentioning
confidence: 99%